Complete Python Web Course : Build 8 Python Web Apps - Salvatierra, Jose (Packt Publishing, 2019)
Build Python web applications from beginner to expert using Python and Flask About This Video Hands-on learning will ensure you're absorbing everything Gain a real understanding of the concepts of software development, design, and operations In Detail Complete Python Web Course: Build 8 Python Web Apps will boost your understanding and skills and may well, with work and patience, result in an income boost or a career change. It is a one-stop-shop covering everything you need to inspire you to create Python web applications that engage visitors and provide them with value. In addition, I'll always be available to help you further your learning and explore more avenues for success. What do you have to do? You'll have immediate access to eight carefully designed sections, each teaching you to create a web application using Python. I've created thorough, extensive, but easy-to-follow content you'll easily understand and absorb. I recommend taking your time, as software development doesn't happen overnight. Each section should take approximately one week, including developing the weekly challenge, reading around the subject, and practicing further. You'll have all the knowledge you need. We introduce our database of choice, MongoDB, and then create our first Python web application: a blog where users can register and publish posts. Then we create a fantastic Python web application to notify you when prices of items in online stores go down; a useful web app! During all this, we'll be learning about deploying our Python web applications, scaling to thousands of users, and mastering usability and security issues. By the time you're done with the course, you'll have mastered the basics and gained extensive knowledge of Python and web development; this will allow you to easily continue learning and developing more and more advanced and engaging web applications. It doesn't matter how old you are or what you do professionally. I guarantee that anyone can benefit from learning web development and Python, but especially web application development.